Analisis Perbedaan Pendapat Ulama tentang Membasuh Kepala dalam Berwudhu Studi Komparatif Mazhab Fiqih - Wahyuni Pohan; Julia Barus; Ali Adhar; Khotami Al Farizi; Wahyudi Batu Bara (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Washing the head is one of the most important pillars of ablution which has a strong legal basis contained in the Koran and hadith. However, in this case the scholars have differences of opinion regarding the scope and method of valid head washing, especially among the four main schools of thought in Islamic jurisprudence, namely (Maliki school, Syafi'i School, Hanafi School, and Hanbali School). This research aims to analyze these differences of opinion comparatively, by reviewing the arguments used, the legal istinbath method, and its implications in terms of the daily practices of Muslims.